Peran Kiyai dalam Melestarikan Budaya Bawean di Pondok Pesantren Penaber - Abdul Hadi Rohmani; Defi Dachlian Nurudiana; Ari Kartiko (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
Kyai at Islamic boarding schools do not only focus on their students studying religion, but there are also many kiyais who have begun to open the sensitivity of their students to care about the culture of the local community. Santri are not only taught religious knowledge and yellow books, but also serve the community. One form of community service that can be done is to preserve local culture. Culture is a nation's wealth that is passed down from generation to generation. Along with advances in technology and the influx of foreign cultures that penetrate into various lines of life, local people's culture will decline and even become extinct if the nation's younger generation does not pay serious attention to this ancestral heritage. Therefore, there is a need for joint efforts so that this finite national heritage continues to exist. The results of this study indicate that: 1) the clerics view that the culture of the Bawean people will increasingly be forgotten if it is not maintained properly, is not taught to the younger generation, is not conveyed with good speech, and is not given an example of good behavior. in time Bawean will lose the characteristics and cultural identity of its people, 2) The role of the kiai as a motivator and modifying forms of artistic activity. Bawean cultural learning is carried out in between student activities through reciting books, reciting art, reciting batik and reciting music. 3) There are two motives behind the kiai's efforts to preserve Bawean culture, namely internal motives and external motives.